STRATEGI MEMBENTUK KARAKTER SEMANGAT KEBANGSAAN ANGGOTA AMBALAN KYAI MOJO DAN NYI AGENG SERANG - Ismaya, Erik Aditia; Romadlon, Farid Noor (Universitas Muria Kudus, 2017)
The purpose of this study is to analyze the strategy of character formation of national spirit of Ambalan Kyai Mojo and Nyi Ageng Serang members based in MA Nahdhlotul Muslimin Undaan Kudus. This research uses qualitative approach with field study method and descriptive research type. Data collection using observation and interview method. Data validity using source triangulation techniques and data were analyzed using Miles-Huberman interactive model. The results showed that in order to form the character of the national spirit of scout members Ambalan Kyai Mojo and Nyi Ageng Serang, the strategy pursued is by holding a regular exercise. There is also a Scout Work Unit (SAKA) exercise to educate and train members according to their interests. Members of Ambalan Kyai Mojo and Nyi Ageng Serang are members of SAKA Bhayangkara (Police), SAKA Pandu Wisata (Culture and Tourism Service), SAKA Wana Bakti (Perhutani) and SAKA Wira Kartika (KODIM). The spirit of nationality continues to grow and develop in the soul of every member of the scout Ambalan Kyai Mojo and Nyi Ageng Serang when inducted into Bantara Enforcer. Not all members of Ambalan Kyai Mojo and Nyi Ageng Serang can pass and escaped and be sworn in to Bantara Enforcers because of the rigorous and tough exam must be taken. Tri Satya is the sacred promise of every Bantara Enforcer when inaugurated by the coach. Tri Satya and Dasa Darma spirit is what makes every Enforcer Bantara Ambalan Kyai Mojo and Nyi Ageng Serang become a patriot plenary.